Contributions to the descriptive and comparative anatomy of the cranium of the Cape fruit-bat Rousettus aegyptiacus leachi Smith - Jurgens, J. D. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1962.